Cognition in vestibular disorders: state of the field, challenges, and priorities for the future - Smith, Laura J.; Wilkinson, David; Bodani, Mayur; Surenthiran, S. S. (Frontiers in Neurology, 2024)
Vestibular disorders are prevalent and debilitating conditions of the inner ear and brain which affect balance, coordination, and the integration of multisensory inputs. A growing body of research has linked vestibular disorders to cognitive problems, most notably attention, visuospatial perception, spatial memory, and executive function. However, the mechanistic bases of these cognitive sequelae remain poorly defined, and there is a gap between our theoretical understanding of vestibular cognitive dysfunction, and how best to identify and manage this within clinical practice. This article takes stock of these shortcomings and provides recommendations and priorities for healthcare professionals who assess and treat vestibular disorders, and for researchers developing cognitive models and rehabilitation interventions. We highlight the importance of multidisciplinary collaboration for developing and evaluating clinically relevant theoretical models of vestibular cognition, to advance research and treatment.